Real-time Visualization of Phospholipid Degradation by Outer Membrane Phospholipase A using High-Speed Atomic Force Microscopy. Issue 7 (7th April 2017) - Rangl, Martina; Rima, Luca; Klement, Jessica; Miyagi, Atsushi; Keller, Sandro; Scheuring, Simon
Abstract: Phospholipases are abundant in various types of cells and compartments, where they play key roles in physiological processes as diverse as digestion, cell proliferation, and neural activation. In Gram-negative bacteria, outer membrane phospholipase A (OmpLA) is involved in outer-membrane lipid homeostasis and bacterial virulence. Although the enzymatic activity of OmpLA can be probed with an assay relying on an artificial monoacyl thioester substrate, only little is known about its activity on diacyl phospholipids. Here, we used high-speed atomic force microscopy (HS-AFM) to directly image enzymatic phospholipid degradation by OmpLA in real time. In the absence of Ca 2 +, reconstituted OmpLA diffused within a phospholipid bilayer without revealing any signs of phospholipase activity. Upon the addition of Ca 2 +, OmpLA was activated and degraded the membrane with a turnover of 2 phospholipid molecules per second and per OmpLA dimer until most of the membrane phospholipids were hydrolyzed and the protein became tightly packed. Graphical Abstract: Highlights: HS-AFM directly visualizes membrane degradation by the phospholipase OmpLA. HS-AFM monitors diacyl phospholipid rather than monoacyl thioester hydrolysis. OmpLA activity in a phospholipid bilayer is specifically Ca 2 + -dependent. OmpLA dimers hydrolyze about two phospholipids per second.